2015
DOI: 10.1088/2041-8205/815/1/l16
|View full text |Cite
|
Sign up to set email alerts
|

Propagating Disturbances in the Solar Corona and Spicular Connection

Abstract: Spicules are small hairy like structures seen at the solar limb mainly at chromospheric and transition region lines. They generally live for 3-10 minutes. We observe these spicules in a south polar region of the Sun with a coordinated observations using the Interface Region Imaging Spectrograph (IRIS) and the Atmospheric Imaging Assembly (AIA) instruments on board the Solar Dynamics Observatory. Propagating disturbances (PDs) are observed everywhere in the polar off-limb regions of the Sun at coronal heights. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…In the simulation, we only use the time scale of spicular activities that are found to be highly correlated with quasi-periodic propagating disturbances in polar plumes (Jiao et al 2015;Samanta et al 2015).…”
Section: Propagating Disturbances In Polar Plumesmentioning
confidence: 99%
“…In the simulation, we only use the time scale of spicular activities that are found to be highly correlated with quasi-periodic propagating disturbances in polar plumes (Jiao et al 2015;Samanta et al 2015).…”
Section: Propagating Disturbances In Polar Plumesmentioning
confidence: 99%
“…These loops have long been known to be permeated by propagating coronal disturbances (PCDs): rapid (∼100 km s −1 ) intensity disturbances whose exact nature remains unknown. While it is clear that PCDs that originate from sunspot umbrae are caused by sound waves, it is less clear whether waves or flows cause these PCDs in plage regions, with both receiving observational and theoretical support (e.g., de Moortel et al 2002aMoortel et al , 2002bDe Pontieu et al 2005;De Moortel 2009;De Pontieu & McIntosh 2010;Verwichte et al 2010;De Moortel & Nakariakov 2012;Ofman et al 2012;Tian et al 2012;Wang et al 2013;Petralia et al 2014;De Moortel et al 2015;Samanta et al 2015;Bryans et al 2016). We also take advantage of recent developments in spicule modeling (Martínez-Sykora et al 2016, 2017) that appear to show coronal heating associated with spicules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several authors have reported that small scale jets and spicules at transition region and chromosphere are associated with with PDs seen in polar plumes and polar coronal holes Jiao et al 2015;Samanta et al 2015;Bryans et al 2016;Yuan et al 2016). Reflections of propagating slow waves were also reported in hot and flaring coronal loops using AIA (Kumar et al 2013(Kumar et al , 2015 and XRT observations (Mandal et al 2016).…”
Section: Introductionmentioning
confidence: 99%